La bienveillance en éducation au prisme de la notion de caring : pour un renouveau des pédagogies actives ? - Thierry Piot (Université de Provence, 2018)
The union "benevolence-requirement" is a central notion of the law. On an epistemological level but also a practical level, the notion of benevolence is related to the concept of caring resulting from an alternative way of thinking born in the USA in the years 1980 and which focuses on people in vulnerable situations. At first, we present this concept of caring through its use in care environments. But we can consider, with Noddings, that in a certain way children who have educational difficulties are also vulnerable people. We suggest to formalize a link between benevolence in education and active pedagogies, notably from two vectors: taking into account the rhythm of learning and the space given to allow use of dialogue in the classroom. However, it seems that the notion of benevolence still remains a fragile priority in the classroom.